What is Entrepreneurial Fear of Failure? - Stievan Kurniadi Halim; Desman Hidayat; Yuli Eni; Erick Fernando (Binus Business Review, 2023)
Fear of Failure (FoF) is not exclusive to entrepreneurship. The concept is stemmed from behavioral studies in psychology. Although entrepreneurship is similar in a performative context, entrepreneurship measures of success still need to be defined. Uncertainties combined with social stigmas of entrepreneurial failure have significantly constrained the growth of entrepreneurship. The aim of the research was to map the literature regarding FoF in an entrepreneurial context. The research sought to understand how much the subject was known, how it was measured, and what factors influenced it. The research applied a systematic literature review study by adopting the PRISMA 2020 statement method and finding 41 articles that specifically studied the subject. It identified a growing interest in the subject, novel reconceptualization, and a few socio-cultural factors influencing FoF in the entrepreneurial context. Then, an experimental measurement scale was also developed. The analysis shows that many articles in FoF are exploratory, with the qualitative approach being the most utilized. Then, GEM data are the most used source in these studies. The research also identifies popular theories, sample regions, methods of measurement, and factors influencing FoF. The result concludes that the topic needs to be explored more, implying many potential areas and formative constructs for future research.